Attitudes of US Obstetricians Toward a Combined Tetanus-Diphtheria-Acellular Pertussis Vaccine for Adults - Sarah J. Clark; Soukaina Adolphe; Matthew M. Davis; Anne E. Cowan; Katrina Kretsinger (Hindawi Limited, 2006)
Objective. To describe obstetricians' perspectives related to tetanus-diphtheria-acellular pertussis (Tdap) vaccination of mothers and other adults in close contact with infants. Methods. Mail survey of national random sample of 400 obstetricians . Results. Response rate was 54%. Most respondents would likely recommend Tdap for women during the postpartum hospital stay (78%) or during pregnancy (69%) if a national recommendation was issued. Expected barriers were knowing the date of patients' most recent Td booster (74%) and patient resistance (46%). Most felt that obstetricians have a role in promoting and administering Tdap vaccine to adults other than mothers likely to come in close contact with infants. Conclusion. Obstetricians are likely to agree with the recent provisional US recommendation to administer Tdap to postpartum mothers and other adults expected to come in close contact with infants. Obstetricians would also be likely to support a potential recommendation to administer Tdap during pregnancy. Barriers to adoption of new Tdap vaccine recommendations should be monitored.